2016
DOI: 10.1177/1742715015574319
|View full text |Cite
|
Sign up to set email alerts
|

Family, feudalism and selfishness: Looking at Indonesian leadership through a wisdom lens

Abstract: Using Social Practice Wisdom (SPW) as a conceptual lens, we shed new light on destructive, selfish leadership and its negative effects. Our study highlights the negative effects on followers of leaders' selfishness, as well as lack of empathy and inauthenticity. Our work also sheds light on new cross-cultural leadership challenges in emerging economies like Indonesia. Analysis reveals deep tensions between Indonesian leaders' tendency to position themselves in self-serving discourses of feudalism and family, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 78 publications
0
7
0
1
Order By: Relevance
“…So, while encouraged to pursue public leadership, women have to ensure the well‐being of their family. The cultural values in Indonesia are predominantly influenced by Javanese patriarchy mixed with Islam and other ethnic values emphasizing the integration of family life (Oktaviani et al., 2016). Hence, for many women, success is defined not only based on how triumphant they are in the public domain (such as achieving leadership) but also on their integration of family and work life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, while encouraged to pursue public leadership, women have to ensure the well‐being of their family. The cultural values in Indonesia are predominantly influenced by Javanese patriarchy mixed with Islam and other ethnic values emphasizing the integration of family life (Oktaviani et al., 2016). Hence, for many women, success is defined not only based on how triumphant they are in the public domain (such as achieving leadership) but also on their integration of family and work life.…”
Section: Discussionmentioning
confidence: 99%
“…Because Indonesia does not constitutionally adopt an Islamic ideology, it is considered a quasi‐secular country (Fenwick, 2016). Its explicit ideology is Pancasila (Oktaviani et al., 2016). Historically, the people of the Indonesian archipelago converted to Islam in the 14th century, mainly through trade, peaceful preaching, and cultural assimilation (Azra, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hegemonic forms of femininity are continually contested in public discourses. Considering Indonesia as a democratic Muslim‐majority society with its cultural characteristics but also open to various influences, discourses, and hegemonic power (Oktaviani et al., 2016), manifestations of idealized femininity in society, for example, traditional Indonesian idealized femininity or neoliberal postfeminist forms of ideal femininity, still conceal hidden forms of patriarchal values or feminist repudiation that is not fully supportive of women's claim to leadership rights (Oktaviani et al., 2021). In recent years, there also has been increasing opposition to women's leadership due to the increasing Islamism in the country (Van Bruinessen, 2013).…”
Section: Gramscian Concept Of Hegemonic Femininitymentioning
confidence: 99%
“…A study conducted in Indonesia (Oktaviani et al, 2016) found that while paternalistic leaders were perceived as hierarchical parental figures, ingrained elements of feudalism, politics of friendship, family and favouritism influenced these leaders to be self-serving, corrupt and often inclined towards authoritarianism. Furthermore, paternalistic leadership has been compared to 'benevolent dictatorship' (Northouse, 1997).…”
Section: Paternalistic Leadershipmentioning
confidence: 99%